PENGARUH FAKTOR DEMOGRAFI DAN PERSONALITY TERHADAP KEAHLIAN DALAM END USER COMPUTING (Studi Kasus Guru dan Karyawan Administrasi pada Sekolah Menengah Atas Negeri di Kotamadya Yogyakarta) - Wisnubroto, Petrus (SENATIK STT Adisutjipto, 2013)
This study aims to analyze the influence of demographic factors ( age , gender , education , experience ) and personality factors ( computer anxiety , computer attitude , math anxiety ) to the end user computing expertise of personnel either partially or simultaneously . Models the influence of the demographic variables and personality skills in end user computing research model replicated from Harrison and Rainer (1992 ) and the research model and Gudono Rifa (1998). The study was conducted on teacher and administrative employees of State High School I to XI in Yogyakarta Municipality considering charging adminsitrasinya teacher certification performed with computerized online program for you State , appropriate curriculum in 2013 all teachers in the learning process to educate students using computerized , so too the acceptance of new students each academic year always use the on-line computerized . Thus both teachers and administrative staff are required to have expertise in End user Computing . So the research conducted to analyze the influence of demographic factors and personality to expertise in End User Computing. The results showed that demographic factors (age - gender - experience) has a direct influence on the expertise in end user computing 0 , 001 ; 0 , 027 ; 0,007 . Personality factors of computer anxiety (fear - Anticipation 0.057) ; computer attitude (Intimidation 0.05) has a direct influence on the expertise in end user computing . The results were quite surprising is the demographic factors (educational 0.117) , personality factors of computer attitude (0.760 pessimism - optimism 0.150) ; math anxiety (0.334) is not significant enough to expertise in end user computing . To improve performance in the Public High Schools in Yogyakarta municipality with regard to the introduction of new technology on- line computerized system above , need to be considered in decisions about withdrawal of the human resources , training and implementation of computer education for personnel and equipment. Provision of adequate facilities is expected to increase its expertise in end user computing , which in turn improves the performance of State High School and individual performance